Legacy of Dilmun: The Roots of Ancient Maritime Trade in Eastern Coastal Arabia in the Fourth/Third Millennium B.C. - Piesinger, Constance Maria
Ph.D. Dissertation; Supervisor: J. B. Stoltman. Order No. DA8400508. - Cf. DissAbstr 44/12 (June 1984) 3733-A.